2018
DOI: 10.1038/s41598-018-21600-w
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme inhibitor reduces scar formation by inhibiting both canonical and noncanonical TGF-β1 pathways

Abstract: Angiotensin-converting enzyme inhibitors (ACEIs) can improve the fibrotic processes in many internal organs. Recent studies have shown a relationship between ACEI with cutaneous scar formation, although it has not been confirmed, and the underlying mechanism is unclear. In this study, we cultured mouse NIH 3T3 fibroblasts with different concentrations of ACEI. We measured cell proliferation with a Cell Counting Kit-8 and collagen expression with a Sirius Red Collagen Detection Kit. Flow cytometry and western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 52 publications
6
37
0
Order By: Relevance
“…As an upper reaching signal molecule, TGF-β regulates the expression of multiple downstream signaling molecules involved in scar formation via both canonical and noncanonical pathways 25 . The TGF-β1/Smad2/3 pathway is considered as one of the most important signaling pathways in scar formation because it supports the overproduction of ECM components and the over-proliferation of fibroblasts, which was confirmed in our previous study 26,27 . Thus, down-regulating the expression of the TGF-β1/Smad2/3 pathway is a promising strategy in scar management.…”
Section: Discussionsupporting
confidence: 80%
“…As an upper reaching signal molecule, TGF-β regulates the expression of multiple downstream signaling molecules involved in scar formation via both canonical and noncanonical pathways 25 . The TGF-β1/Smad2/3 pathway is considered as one of the most important signaling pathways in scar formation because it supports the overproduction of ECM components and the over-proliferation of fibroblasts, which was confirmed in our previous study 26,27 . Thus, down-regulating the expression of the TGF-β1/Smad2/3 pathway is a promising strategy in scar management.…”
Section: Discussionsupporting
confidence: 80%
“…It is possible that high level of ACE and chymase enzyme activity and subsequently high concentration of angiotensin II is involved in scar formation . Angiotensin II causes increase in collagen synthesis but losartan is an AT 1 receptor antagonist that inhibits collagen production . Our results showed that losartan reduces pliability significantly in keloids and hypertrophic scars probably by antifibrotic effects.…”
Section: Discussionmentioning
confidence: 54%
“…Stimulation of human fibroblasts isolated from keloid, hypertrophic scar, and normal tissues by TGF‐β leads to the increment of CTGF expression and CTGF may be a fibrogenic mediator of angiotensin II . It is reported that losartan can reduce TGF‐β, phosphorylated SMAD2/3, phosphorylated TAK‐1, and CTGF signaling …”
Section: Introductionmentioning
confidence: 99%
“…Many articles have concluded that inhibiting broblast proliferation can effectively reduce epidural brosis and reduce scar tissues hyperplasia. Some articles show that the TGF-β1 / Smad2/3 axis is extensively participated in the formation of brosis, and repression of the channel can inhibit the proliferation of broblasts [11,12]. In addition, many studies have indicated that inhibition of broblasts migration and differentiation can also achieve better anti-brotic effects [13,14].…”
Section: Introductionmentioning
confidence: 99%